Implementasi Kebijakan Pembangunan Pos Pemadam Kebakaran di Kecamatan Strategis sebagai Mitigasi Bencana Non-Alam di Kabupaten Gresik (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The development of fire stations (Pos Damkar) in Gresik Regency represents a strategic step to strengthen fire disaster mitigation in a rapidly growing region. New stations in strategic districts such as Manyar, Kebomas, and Driyorejo aim to shorten response times and improve the effectiveness of fire handling. A transformation has also occurred in the role of firefighters, who are no longer merely reactive but also active as community mobilizers, facilitators, and educators. Through education programs, volunteer training, and regular evacuation drills, public awareness of fire prevention is significantly enhanced. Educational programs include the use of fire extinguishers, counseling on electrical short-circuit and gas leak hazards, as well as evacuation simulations in schools and industrial areas. Capacity building is further supported by cross-sector partnerships, involving schools, industries, and private stakeholders. The establishment of fire volunteers strengthens early detection and initial response, accelerating mitigation efforts and reducing losses. Technologies such as Geographic Information Systems (GIS) and integrated communication systems are being applied to improve efficiency and effectiveness. Despite challenges such as limited funding, strategic land availability, and the need for more competent human resources, collaboration with the private sector is expected to address these gaps. Overall, the development of fire stations and the transformation of firefighter roles create an integrated mitigation system based on infrastructure, education, and community empowerment, making Gresik safer, more resilient, and sustainable.